(untitled) (Biological Sciences - PJSIR, 1998)
Seedcotton yield, earliness and boll rot incidence studies on the okra leaf trait against normal leaf were carried out at Cotton Research Institute, Sakrand during 1993. Boll rot incidence of 28.8% was recorded in normal leaf trait as against 7.7% of okra leaf. Thus okra leaf trait reduced the boll rot incidence considerably and the percentage difference over normal was 70.8%. Okra leaf shape was earlier than normal leaf shape and formed and opened more number of bolls per plant thus out yielded normal leaf cultivar by giving 3002 kg ha’ seedcotton yield as compared with 2870 kg ha’.